Masculino & Feminino: a androginia na música brasileira (1966-1985) - Baena, Pâmela Keiti (2022)
Androgyny proved to be an aesthetic expression that was very present in the 20th century, particularly with regard to the western music scene. From the 1970s onwards, groups and artists incorporated this aesthetic into their musical and theatrical performances, bringing the importance of the visual to the fields of sound and interpretation. The music represented by the image. But where does this aesthetic come from and what elements can be considered androgynous in musical performance? What was the importance of this artistic movement in contemporary Brazilian music? Can it be thought of as a continuous movement or are they, in each epoch, isolated forms of expression? To guide these questions, the androgynous aesthetics in Brazilian music album covers and inserts during the second half of the 20th century, more precisely between 1966 and 1985, under the influence of social movements in the context of sexual liberation , counterculture and the explosion of rock facilitated by the media around the world and, in Brazil, in the context of the Military Regime and the censorship of artistic productions, influenced by the tropicalist movement. Using analysis of documental sources according to historiography as a research methodology, it was intended to know the history of androgyny; point out its importance to the English musical movement called glam rock; to weave connections between Brazilian artists who fit into such a category; and to reflect on the meanings of these approaches in music, facing a society in which gender binarism has been questioned. It was concluded that androgyny operates through vagueness and ambiguity, with the intention of transgressing any form of normativity.